Plea Bargaining System as a Non-Litigation Settlement In The Framework of Repositioning Criminal Justice In Indonesia - Almi, Ara Annisa (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
In its development, Plea Bargaining was accommodated into a written rule in 1970, when the court decided the case of Brady v United States. The Plea Bargaining System uses methods in civil law to resolve criminal cases. Indonesia's legal system can adopt the Plea Bargaining concept into the criminal justice system. The drafting team introduced the term Plea Bargaining in the Academic Paper of the Draft Criminal Procedure Code (NA RUU KUHAP). This design is considered different from the initial concept applied in other countries. Therefore, an analysis of legal protection and certainty for justice seekers (justiciabelen) is needed. The research method used is normative juridical, namely by studying secondary data and understanding law as a set of rules related to Plea Bargaining.